Urgencias Del Latinoamericanismo en Tiempos de Globalización Conflictiva : Tributo a John Beverley - Monasterios Pérez, Elizabeth (Literatura y Cultura Ser., 2020)
"Urgencias del latinomericanismo en tiempos de globalización conflictiva is a collective book written in the heat of the challenges that the current world reconfiguration is posing to Latin Americanism, pushing it to join the horizon of what is already a conflicted globalized world and ignorant of the fractures that it itself generates. Discussing with what strategies, uncertainties, self-critical will and historical burden does Latin Americanism move towards this global-becoming of the world, orients the book project and allows addressing some of the most pressing questions of Latin American critical thought regarding the viability / unfeasibility of the social utopias and cultural sovereignties that are (still) disputed in the region. Crucial in the project of this book is a critical dialogue with the debates, polemics and theoretical constructions posed by the work of the challenging Latin Americanist who is John Beverley"--